Engagement Enhancement Strategy Between Nurses Public Hospital and Private Hospital Through Improving Perceived Organization Support, Selfefficacy and Servant Leadership (Comparative Study Using QualitativeAnalysis) - Annisaa Soeyono; Didik Notosudjono; Widodo Sunaryo (International Journal Labs, 2026)
Nurse engagement is an important factor in improving the quality of health services, patient safety, and hospital performance. The level of nurse engagement can differ between public and private hospitals due to differences in organizational characteristics, management systems, work culture, and leadership styles. This study aims to explore strategies for increasing nurse engagement based on the context of both types of hospitals. The study uses a qualitative approach with data collection techniques through literature review and observation. Data analysis was conducted through the stages of data reduction, data presentation, and conclusion drawing. The results show differences in the level of nurse engagement between government and private hospitals. Government hospital nurses have high engagement indicators in productivity, ownership, loyalty, vigor, and absorption, while private hospital nurses excel in career development and dedication. Perceived organizational support, self-efficacy, and servant leadership had a positive and significant effect on nurse engagement in both types of hospitals, both partially and simultaneously. However, the difference in the effect of each variable partially was not significant between the two hospitals. This study recommends the formulation of strategies to increase engagement through socialization programs, organizational support and self-efficacy training, and strengthening servant leadership.